History of probabilistic seismic hazard assessment studies and seismic zonations in mainland France - Beauval, Céline; Bard, Pierre-Yves (Comptes Rendus. Géoscience, 2022)
This article aims to provide an overview of successive seismic zonations in mainland France and probabilistic seismic hazard studies performed over the previous ${≈ }$30 years. A short presentation is given on the engineering and regulatory framework that shapes the background of seismic zonation and hazard studies, followed by a scientific overview of published probabilistic seismic hazard estimations. The components of these past PSHA studies are summarized (seismic source models, ground-motion models, management of uncertainties). The evolution of hazard estimates with time is displayed for a set of representative cities. Finally, three generations of official seismic zonation maps in France are presented (1967, 1986, 2004), and the evolution of methods and results is highlighted. This review shows that the academic community has previously had little involvement in this topic. As current zonation relies on outdated models, there is an opportunity for scientific and engineering communities to efficiently work together to build the next generation of probabilistic seismic hazard models for France.